UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPA SUB STRUKTUR TULANG DAUN MELALUI MODEL PEMBELAJARAN PORTOFOLIO PADA SISWA KELAS VII.A SMPN 2 SUNGAI TARAB - Admi, Zul (STKIP Pesisir Selatan, 2018)
Based on the learning outcomes of class VII.A students of Tarab River Junior High School 2 in the Science subject of Leaf Bone Sub-Structure it was found that student learning outcomes in science subjects were still low. The average student learning outcomes are still under the KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in science subjects through a Portfolio learning model in Class VII.A SMPN 2 Sungai Tarab District Tanah Datar. This research is a classroom action research. The procedure of research in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 20 students of Class VII.A SMPN 2 in Tarab River. Research data was collected using observation sheets and daily tests. Data were analyzed using percentages. Based on the results of research and discussion that have been put forward, it can be concluded that the Portfolio learning model can improve student learning outcomes in science subjects at Tarab River 2 Junior High School. Student learning outcomes from cycle I to cycle II. Student learning outcomes in the first cycle were 59.62 (Less) increased to 83.82 (good) with an increase of 24.21